Supplementation of TGF-Beta3 in low serum media promotes chondrogenesis of BMSCs - Alfaqeh, Hamoud Hussein Mohammed; Idrus, Ruszymah; Chua, Kein Hui; Saim, Aminuddin (UKM, 2017)
ABSTRACT Tissue engineering has emerged as a new promising field that allow in vitro construction of whole transplantable tissue. Recently, bone marrow stem cells (BMSCs) fulfil the requirements as appropriate cell source that is renewable for cartilage tissue engineering since they were able to form hyaline-like cartilage in vitro and in vivo when cultured in media supplemented with specific growth factors. This study aimed to examine the potential of BMSCs chondrogenesis in vitro and in vivo. BMSCs were isolated from sheep and divided into a test group and control group. Control group was cultured in medium supplemented with 10% fetal bovine serum (FBS). Test group was cultured in medium supplemented with 1% FBS, 1% ITS, 5ng/mL TGF-ß3, 50ng/mL IGF-1, 40 ng/mL L-proline, 100 nM dexamethasone and 50 μg/mL ascorbic acid-2 phosphate. The experiment was carried out on athymic nude mice. Cell aggregates were formed in test group and indicated the early chondrogenesis in cell culture. Later, cells-fibrin constructs were made and implanted subcutaneously into nude mice for 5 wks, then explanted for histological examination and glycosaminoglycans (GAG) quantification. Test group constructs showed higher cartilage matrix synthesis as confirmed by Safranin O staining and GAG production. These results demonstrated the effectiveness of low serum media supplemented with TGF-ß3 in promoting chondrogenesis in BMSCs. Keywords: bone marrow, cartilage, chondrogenesis, growth factors, low serum media, stem cells